2011
DOI: 10.1017/s0007114511001851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neutering on food intake, body weight and body composition in growing female kittens

Abstract: To understand the effects of neutering on food intake, body weight (BW) and body composition in kittens, data from an unrelated study were subjected to post hoc analysis. A total of twelve pairs of 11-week-old female littermates were randomly assigned to either a neutered group (neutered at 19 weeks old) or an entire group (kept entire) and offered free access to a dry diet until the age of 1 year. Neutered kittens exhibited increased food intake and increased BW after neutering (both P, 0·00 001). Food intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 13 publications
(15 reference statements)
4
34
1
4
Order By: Relevance
“…Neutering was performed as part of normal veterinary practice at WALTHAM and occurred at one of two time points, one defined as early (early neutering; EN), at 19 weeks of age and the other, defined as conventional (conventional neutering; CN), at 31 weeks of age. Whilst neutering may occur earlier (6–12 weeks of age), 19 weeks is consistent with a previous study ( 11 ) , where cats were fed a dry diet ad libitum . The choice of 31 weeks as a later time point is not a specific ‘conventional’ time but is consistent with neutering following sexual development and was primarily to allow an entire control group for the longest time within current husbandry practice at WALTHAM.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…Neutering was performed as part of normal veterinary practice at WALTHAM and occurred at one of two time points, one defined as early (early neutering; EN), at 19 weeks of age and the other, defined as conventional (conventional neutering; CN), at 31 weeks of age. Whilst neutering may occur earlier (6–12 weeks of age), 19 weeks is consistent with a previous study ( 11 ) , where cats were fed a dry diet ad libitum . The choice of 31 weeks as a later time point is not a specific ‘conventional’ time but is consistent with neutering following sexual development and was primarily to allow an entire control group for the longest time within current husbandry practice at WALTHAM.…”
Section: Methodssupporting
confidence: 89%
“…The total energy requirement (TER) study reported here (female cats neutered at 19 and 31 weeks) in the left-hand panel is compared with data from two previous trials that were carried out at the WALTHAM Centre for Pet Nutrition at different times and with different dietary management regimens. The ‘self-regulated’ trial ( 11 ) (middle column) describes data from a study where the intake and weight data were obtained from female cats fed a commercial dry diet ad libitum and where cats neutered at 19 weeks of age were compared with a group that remained entire to 1 year of age. The macronutrient profile (MNP) food selection trial (right-hand column; AK Hewson-Hughes, VL Hewson-Hughes, R Staunton and SJ Simpson, Raubenheimer D, unpublished results) measured daily intakes from female cats offered excess of each of three wet diets differing in macronutrient composition at each meal, enabling them to select a macronutrient composition and eat ad libitum , where the neutered group was neutered at 26 weeks of age and compared with an entire group to 1 year of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overweight in cats is a known risk factor for lameness (Scarlett and Donoghue 1998) as well as for traumatic fractures at the capital femoral epiphysis (Craig 2001). Unlike the plethora of studies comparing obesity in gonadectomised versus entire animals regardless of time of gonadectomy (Fettman and others 1997, Robertson 1999, Allan and others 2000, Martin and others 2001, Lund and others 2005, Colliard and others 2009, Courcier and others 2010), few studies have specifically addressed the relationship between age at time of gonadectomy and the development of overweight in cats (Stubbs and others 1996, Root and others 1996b, Alexander and others 2011). It is well established that gonadectomy is one of the important predisposing factors for the development of overweight and obesity in cats (Robertson 1999, Lund and others 2005, Colliard and others 2009, Courcier and others 2010, Joyce and Yates 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in laboratory settings has established the importance of reducing cats' post-neutering energy intake through controlled feeding ( 11 ) as well as the efficacy of feeding a low-energy-dense diet in decreasing post-neutering weight gain in cats ( 7 ) . However, methods that are successful under controlled laboratory conditions have the potential to be less effective in a real-world setting ( 9 ) .…”
Section: Discussionmentioning
confidence: 99%